"Pacience is an Heigh Vertu": Managing the Canterbury Tales Project Via Textual Communities. Issue 1 (9th November 2021) - Dase, Kyle; Atkings, Nicole
Abstract : This article functions as both a reflective essay and a pedagogical account of the second phase of the Canterbury Tales Project and the various successes and challenges that unfolded throughout that process. Our focus is how the project both managed the transcription team working locally at the University of Saskatchewan and facilitated transcription workshops abroad. We detail our training process and the transcription workflow as facilitated via the Textual Communities environment. We also examine and evaluate the causes of the project's challenges—often the result of institutional pressures or technological changes—and our reactions to those challenges, emphasizing successful strategies. Finally, we proffer future changes for the project that we believe would have made considerable positive impact if implemented from the outset of phase two and still have potential as helpful resources now. It is our hope that in detailing our process we can help other large DH projects mimic our successes and, perhaps even more importantly, avoid any pitfalls that challenged us.